Who Gets the 'Gift of Time' in Australia? - Edwards, Ben; Taylor, Matthew; Fiorini, Mario (My University, 2011)
The practice of ‘academic red-shirting’ (parents delaying enrolment in primary school for a year after their child is first eligible) is becoming more common in the developed world. The idea behind this practice is that the ‘gift of time’ enables children to develop cognitively and emotionally so that they are more school-ready than their peers. Little is known about the factors associated with delayed school entry in Australia. In this paper we begin to fill this gap in the Australian research using data from the Longitudinal Study of Australian Children. We estimate that 14.5 per cent of school entrants in 2005 had been delayed from the previous year, the first national estimates of delayed entry. The rates of delayed school entry vary markedly between states and territories with New South Wales having particularly high rates of delayed entry (31.3 per cent in 2005). Parental decision-making about delaying a child’s entry to school appears to be most influenced by state and territory entry age policies with only a few other factors found to be statistically significant. Children who are less able to persist at tasks and boys are more likely to be delayed entrants. The decision to delay a child’s entry to school is also more likely if English is the mother’s first language and if the family lives in a non-metropolitan area.
Australian Review of Public Affairs
Keywords: Education and Training; Education and Training -- school readiness; Education and Training -- Early Childhood; Learning, education and training; Education and Training; Early Childhood; school readiness; Learning, education and training